Planning of Air Conditioner Cooling Load In The Dean Room Of The Faculty Of Engineering and Information Technology University Of PGRI Semarang - Supriyadi, Slamet; Farikhah, Irna; Suhartono, Suhartono (UI Scholars Hub, 2022)
The specification of the cooling load or chiller in the FTI UPGRIS dean's room currently requires a review of the distribution of cooling air in the room due to the number of electronics and occupants in the room and the size of the air conditioner. Therefore, the room must be taken into account to prevent insufficient cooling load, As a result, it is impossible to reach the desired temperature and humidity set. The FTI Dean's room has an air conditioner with a cooling capacity of 1 unit. It should be able to cover the amount of cooling in the room. To calculate the cooling load borne by the room of the Dean of the FTI UPGRIS, an analysis of the calculation of the cooling load was carried out to determine the number of cooling units needed to provide sufficient cooling in the Dean Room of the FTI UPGRIS. Data collection techniques obtained from the results of research in the room used quantitative research. quantitative data that the largest load is the sensible load 322753.21 Btu/hr, and the latent load is 47152.52 Btu/hr with the total cooling load 369905.73 Btu/hr + 5% Safety Factor (SF) 388.401.01 Btu/hr at 16.00 WIB. Why does the highest load occur at 13.00 WIB, this is due to the maximum load or the peak of the cooling load in the FTI Dean's room. And in terms of the load density of the FTI Dean's room of 388,401.01 Btu/hr divided by the building area of the FTI Dean's room of 530.76 ft^2, the result is that the cooling load density is 731.78 (Btu/hr) per ft^2. From research in the FTI Dean's room, the result was 113.83 Kwatt. The selection of AC units is adjusted to the size of the room, the larger the room that is cooled in the FTI Dean's room, 2 AC units are installed with a power of 1.5 pk with a capacity of 12,000 Btu/hr.